2011
DOI: 10.1039/c1nj20377k
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral niobium cluster-based solid state halides and oxyhalides: effects of the cluster condensation via an oxygen ligand on electronic and magnetic properties

Abstract: International audienceThe influences of an oxygen ligand on the structural, magnetic and electronic properties of octahedral niobium cluster-based oxides and oxychlorides are reported. The Nb6 metal cluster is edge-bridged by twelve inner ligands and additionally bonded to six apical ligands to form Nb6Li12La6 units (L = Cl, O) wherein oxygen and chlorine are perfectly ordered. Oxygen favours the interconnection of clusters via double Oi-a/Oa-i bridges in a similar way to the double Si-a/Sa-i bridges found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] If compounds from high temperature cluster syntheses are used directly as precursors for subsequent chemical reactions, quite often difficulties are observed in performing stoichiometric reactions, since the compounds from the solid state chemical reactions are accompanied by side products and/or unreacted starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] If compounds from high temperature cluster syntheses are used directly as precursors for subsequent chemical reactions, quite often difficulties are observed in performing stoichiometric reactions, since the compounds from the solid state chemical reactions are accompanied by side products and/or unreacted starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical studies have shown that replacing one halogen inner ligand by an oxygen atom hardly modify the electronic structure of the cluster unit, whereas a larger number of bridging oxygen ligands destabilises the a 2u level making the ME count of fourteen optimal 21. 29 It has also been shown that the [(M 6 ${{\rm Cl}{{{\rm i}\hfill \atop 9\hfill}}}$ ${{\rm O}{{{\rm i}\hfill \atop 3\hfill}}}$ )${{\rm Cl}{{{\rm a}\hfill \atop 6\hfill}}}$ ] 5− (M=Nb, Ta) isomer of D 3 symmetry with alternate inner oxygen ligands is more stable than the arrangement of C 2 symmetry where the inner oxygen ligands are adjacent 21. The geometry of both isomers of [(Ta 6 ${{\rm Br}{{{\rm i}\hfill \atop 9\hfill}}}$ ${{\rm O}{{{\rm i}\hfill \atop 3\hfill}}}$ )${{\rm Br}{{{\rm a}\hfill \atop 6\hfill}}}$ ] 5− with 14‐MEs have been optimised.…”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations have shown that the inner ligands play a crucial role in the propagation of magnetic interactions in such compounds. Weaker intercluster antiferromagnetic interactions also exist in A x Nb 6 Cl 12 O 2 (A=Rb, Cs) compounds that contain some 15‐ME hexanuclear species 29. In these latter, neighbouring clusters are connected through O i‐a /O a‐i double bridges in two directions 29.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations